Isolation of Aflatoxin B1 from Moldy Foods by Solid-Phase Extraction Combined with Bifunctional Ionic Liquid-Based Silicas - Luwei Fang; Minglei Tian; Xuemin Yan; Wei Xiao (Journal of Analytical Methods in Chemistry)
A solid-phase extraction method was developed by using new bifunctional ionic liquid-based silicas as sorbents to isolate aflatoxin B1 from moldy corn and peanut. Firstly, according to the adsorption efficiency, two sorbents imidazolium chloride-butylimidazolium chloride-based silica (Sil@BIm-Im) and imidazolium chloride-hexylimidazolium chloride-based silica (Sil@HIm-Im) were selected. The RSM was introduced to optimize adsorption conditions such as methanol/water ratio, time, and pH. Sil@HIm-Im, which had the highest adsorption efficiency, was used in SPE as a sorbent. After 2.0 mL of loading samples, washing solvents were optimized as 6.0 mL and 4.0 mL of water for corn and peanut, 2.0 mL of acetonitrile, and 3.0 mL of methanol. 3.0 mL of methanol/acetic acid (2.0% vol.) was investigated as an elution solvent. Finally, 0.009 μg/g and 0.023 μg/g of aflatoxin B1 were obtained in corn and peanut extract with recoveries of 80.0%–103.3% and RSDs of 2.37%–6.58%.